Some Fixed Point Theorems in Intuitionistic Fuzzy Metric Space - Sabri, Raghad I. (Iraqi Journal of Science, 2025)
Mathematics and the applied sciences both heavily rely on fixed point ( theory. Additionally, this theory has several applications in integral equations and differential equations to guarantee the solutions’ existence and uniqueness. theory relies mainly on the Banach contraction principle. Since this idea first appeared, it has gained a lot of attention and there has been a lot of development in this field. In this paper, the concept of generalized Kannan-type() mapping is presented in intuitionistic fuzzy metric space(IFM space), and the theory is proven. The results contain extensions of theory in IFM-space which include the Caccioppoli theorem. Additionally, an instance is provided to illustrate the practical significance of the research’s results